Ukuran Tubuh Ayam Lokal Silangan IPB D-1 Generasi Kelima Umur 2 Sampai 12 Minggu - Lukmanudin, M.; Sumantri, C.; Darwati, S. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2018)
Kampung chicken is Indonesian native chickens that has slow growth. One way to increase growth is crossing. Pelung-sentul-kampung-meat type chicken (IPB D-1) is a chicken from crossing between F1 pelung-sentul (PS) male and kampung-meat type chicken strain cobb (KM) female to produce chicken that has fastly growth and big body size. Factors that need to be examined to find out the bone growth and body structure of chicken is the body size. The aim of the research was to asses body size chicken IPB D-1 generation G4 crosing results with interse at age 2 until 12 weeks. The number of chickens used 33 males and 38 females. The Variables measured every 2 weeks were body weight, shank length, shank circumference, tibia length, femur length, back length, chest circumference, chest width, chest depth, and chest length. Research data were analyzed descriptive. IPB D-1 chicken G5 have a coefficient of diversity 5% to 15% on each variable observed. The fifth generation of IPB D-1 chicken (G5) have a variation body size. Chest length is the best variable to predict the body weight.